The relationship between knowledge of learning strategies, innovativeness and interpersonal communication with Widyaiswara’s ability to manage learning - Wibowo, Sigit; Hartono, Rudi (Technium Social Sciences Journal, 2022)
The objective of the research is to find out the relationship between knowledge of instructional strategy, innovativeness, and interpersonal communication with the ability of instructor to manage instruction. The subject of the research is the instructor at the Vocational Education Development Center Jakarta, with a sample 50 instructors. The three independent variables are knowledge of instructional strategy which is measured by test instrument, the innovativeness and interpersonal communication which are measured by non test instrument, and the dependent variable is the ability of instructor to manage instruction which is measured by non test instrument using the form of observation sheet. The result of the research indicates that: (1) there is positive correlation between knowledge of instructional strategy and the ability of instructor to manage instruction; (2) there is positive correlation between innovativeness and the ability of instructor to manage instruction; (3) there is positive correlation between interpersonal communication and the ability of instructor to manage instruction; and (4) there is positive correlation between knowledge of instructional strategy, innovativeness, and interpersonal communication all together and the ability of instructor to manage instruction. The result of the present study suggest that the ability of instructor to manage instruction can be increased through enhancing knowledge of instructional strategy, innovativeness, and effectiveness of interpersonal communication.